2014
DOI: 10.1155/2014/475175
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metastasis in Bone and Soft Tissue Cancers: A Review of Incidence, Interventions, and Outcomes

Abstract: Bone and soft tissue malignancies account for a small portion of brain metastases. In this review, we characterize their incidence, treatments, and prognosis. Most of the data in the literature is based on case reports and small case series. Less than 5% of brain metastases are from bone and soft tissue sarcomas, occurring most commonly in Ewing's sarcoma, malignant fibrous tumors, and osteosarcoma. Mean interval from initial cancer diagnosis to brain metastasis is in the range of 20–30 months, with most being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 135 publications
5
73
0
4
Order By: Relevance
“…1 Osteosarcoma is characterized by osteoid-producing atypical cells, and tumor cell dissemination is mainly through the bloodstream targeting lungs and other bones. 2 Despite great advances in treatment modalities, the survival rate of osteosarcoma has remained unchanged over the past decades, and the long-term survival rate for individuals suffering from metastatic or recurrent osteosarcoma remains unpromising. 3,4 Therefore, there is an urgent need for further investigations to explore new molecular mechanisms that modulate the carcinogenesis and metastasis of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…1 Osteosarcoma is characterized by osteoid-producing atypical cells, and tumor cell dissemination is mainly through the bloodstream targeting lungs and other bones. 2 Despite great advances in treatment modalities, the survival rate of osteosarcoma has remained unchanged over the past decades, and the long-term survival rate for individuals suffering from metastatic or recurrent osteosarcoma remains unpromising. 3,4 Therefore, there is an urgent need for further investigations to explore new molecular mechanisms that modulate the carcinogenesis and metastasis of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…The production of coagulation activation factors, mainly VEGF-A in OSA, along with the vascular lesion concomitant to the growing of the metastatic tumor has great importance in the occurrence of hemorrhagic vascular lesions, independent if the patient is in the initial or advanced stage of the disease (19). It is believed that this characteristic of intravascular hypercoagulability has favored the adhesion of the neoplastic embolies to the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 30% of the human patients with any kind of cancer develop brain metastasis, however, only 0,8% of them all come from musculoskeletal tumors (osteo and rhabdomyosarcoma) or from soft tissue sarcomas, in this way, the metastasis of OSA to central nervous system is considered rare in all species, independent of primary origin be bone or extraosseous (12,16,19). Despite the rarity even in dogs, Rottweilers are known to have more chances of having brain metastases than other breeds (12).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Ogose et al (6) reported that alveolar soft part sarcoma, extraskeletal Ewing's sarcoma and rhabdomyosarcoma exhibit relatively high incidences of brain metastases. Regarding MPNSTs of the lung, only 21 cases of metastases to the brain have been reported previously (7). Of these 21 cases, the frontal lobe was the most common location for brain metastasis (7).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding MPNSTs of the lung, only 21 cases of metastases to the brain have been reported previously (7). Of these 21 cases, the frontal lobe was the most common location for brain metastasis (7). Metastasis to the brainstem is uncommon and accounts for only 3-5% of all brain metastases (8).…”
Section: Discussionmentioning
confidence: 99%